Review On Different Types of Drag and Drop Mobile App Development Platforms - Joy, Johnsymol (International Journal of Computer Sciences and Engineering, 2025)
A mobile app is a software application designed for use on small wireless devices such as smart phones and tablets rather than desktop or laptop computers. Nowadays thousands of mobile apps are published to the Google Play store or Apple Store. Even a person who has no knowledge on programming languages can create mobile apps, with the help of various mobile app development platforms. Lots of such mobile app development platforms are available today. Some of those are used for creating native apps and some for creating Hybrid apps. Drag and Drop App Builders give non-developer users a solution to build do-it-yourself applications. Such products include features exactly same as design products like visual drag-and-drop tools to make apps. This paper focused on reviewing and familiarizing some efficient drag and drop mobile app builder platforms